The king of the Golden River: a story - Ruskin, John; Turska, Krystyna (Hamish Hamilton, 1978)
Through kindness, a boy regains for himself the treasure his cruel older brothers lost.
Through kindness, a boy regains for himself the treasure his cruel older brothers lost.
Keywords: Fairy tales. / http://id.loc.gov/authorities/subjects/sh85046925